If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3z = 5 + 7y Solving 2x + 3z = 5 + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3z' to each side of the equation. 2x + 3z + -3z = 5 + 7y + -3z Combine like terms: 3z + -3z = 0 2x + 0 = 5 + 7y + -3z 2x = 5 + 7y + -3z Divide each side by '2'. x = 2.5 + 3.5y + -1.5z Simplifying x = 2.5 + 3.5y + -1.5z
| y^2=-7 | | 3(4y-1)=(5y+.5) | | 3/14/7/10 | | 5y+y=42 | | 5-y-y=15 | | 1/3w-9/5=-1/2 | | 2a+5-(a-7)= | | 4x^2+5(4x^2-x)-3x= | | (2535+-1157x+189x^2+x^3)(x+1.5)=0 | | 4b^2+20b+25= | | 4y+2w=7 | | y/-4=3 | | x+xy+x=9 | | (5x+8)(3y-1)= | | (25x^2)-81=0 | | (13+-6x+x^2)(x+195)=0 | | (4x+5)(5y-4)= | | 2cos^2x-3cosx=1 | | (6x-5)*(4x+1)= | | 23/8= | | 2cos^2x=3cos+1 | | (9+-4i^2+-6x+x^2)(x+195)=0 | | (-3z/y^4)^3 | | 4[4(x-7)+1]= | | 4x+6=x-12 | | 2-4x-8x=5 | | (1.6-2x)2= | | -5y-8=-4y-9 | | x/9=x/10-3 | | 17+8=-5(6x-5) | | 4(3x+6)=-28+4 | | 5x^3-45x^2+70x=0 |